Online walking motion generation with automatic footstep placement - Herdt, Andrei; Diedam, Holger; Wieber, Pierre-Brice; Dimitrov, Dimitar; Mombaur, Katja; Diehl, Moritz (Advanced robotics, 2010)
The goal of this paper is to demonstrate the capacity of model predictive control (MPC) to generate stable walking motions without the use of predefined footsteps. Building up on well-known MPC schemes for walking motion generation, we show that a minimal modification of these schemes allows designing an online walking motion generator that can track a given reference speed of the robot and decide automatically the footstep placement. Simulation results are proposed on the HRP-2 humanoid robot, showing a significant improvement over previous approaches.